2022
DOI: 10.35912/ijfam.v4i1.852
|View full text |Cite
|
Sign up to set email alerts
|

Financial statement analysis as a tool for investment decisions and assessment of companies’ performance

Abstract: Purpose: Financial Statement Analysis (FSA) and Interpretation is a vital instruments for good management decision-making in business. The main objective of this study is therefore to determine how firms could use FSA and its interpretation to aid funding and investment decisions and to avert low profitability or low investment returns. Research methodology: Data from the annual report of Nestlé Nigeria Plc are utilized for the Analysis and Interpretation of the financial ratio using descriptive statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…Financial statement interpretation through ratios is vital instrument for sound management decision-making in business (Olayinka, 2022). Application of ratios to interpret financial statements yields immediate cue of firms performance and status to varied users (Abdul-Baki et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial statement interpretation through ratios is vital instrument for sound management decision-making in business (Olayinka, 2022). Application of ratios to interpret financial statements yields immediate cue of firms performance and status to varied users (Abdul-Baki et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial ratio analysis insinuates to meet the basic essentials of all doable investors necessitating all-embracing monetary database (Brearey, 2013;Mary;Wayne, 2010). Financial statement analysis via ratios is a vital instrument for good management decision-making in business (Olayinka, 2022). Divulgence of information contained in ratios metamorphoses management dibs to extend additional information to distinguish firms financial fors and againsts, and innate opportunities and threats (Aripin et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the topic "determinants and impacts of NFR. the studies identified as determinants of NFR or disclosure of key performance indicators (KPIs): corporate governance mechanisms, such as the duality of outside directors and Chief Executive Officer (CEO) (Alonso Carrillo, Priego De La Cruz, & Nunez Chicharro, 2019) and presence of independent directors on the board (Pizzi, Rosati, & Venturelli, 2021); stakeholders pressure for companies operating in environmentally sensitive industries (Krasodomska et al, 2021); company size; profitability, ownership structure, financial position and company age (Moraru, PĂUN, DURA, Dinulescu, & Potcovaru, 2020); firms' market share, their field of activity and ownership structure (Păun, Dura, Mihăilescu, Moraru, & Isac, 2020), firm size and assurance (Venturelli et al, 2017); financial performance (Loprevite, Raucci, & Rupo, 2020;Olayinka, 2022); European policymakers (Venturelli et al, 2017); prior regulation, local institutional characteristics, ownership, industry and auditors (Dumitru et al, 2017). (Mio et al, 2020) found, within the framework of Legitimacy Theory that company size, intangibles, and environmentally-sensitive industry are predicting variables of disclosing non-financial information even after EU Directive implementation, while, from the Agency Theory perspective, the corporate governance mechanism (board size, leverage and ownership dispersion) partially increases, because board size ̶ one of the variables typically employed within agency theory to predict NFR ̶ gained significance in 2017 compared to 2016.…”
Section: Main Research Topicsmentioning
confidence: 99%
“…Judul Penelitian Akuntansi Berbasis: Jumlah Presentasi % a. Budaya Daerah 17 0,14% b. Non Budaya Daerah 3.676 99,56% Total Hasil Riset Akuntansi 3.692 100% Sumber: Data diolah oleh pemateri Berdasarkan tabel 1 sebelumnya, terlihat bahwa total riset akuntansi budaya yang diterbitkan tahun 2020 berjumlah 3.692 riset, akan tetapi dari jumlah tersebut hanya terdapat 17 riset akuntansi dengan konteks kearifan lokal, selebihnya pengembangan pengetahuan akuntansi didominasi oleh kajian akuntansi non kebudayaan, misalnya saja penelitian yang dilakukan oleh (Baribe & Sondakh, 2020), (Chinyamunjiko, Makudza, & Mandongwe, 2022), (Chinyamunjiko et al, 2022), (Dewi, Atmadja, & Darmawan, 2014), (Diana, 2011), (Eka & Arviana, 2018), (Ginting, 2021), (Hasanah.Nur & Siswanti.Tutik, 2019), (Hasni, 2018), (Jayed, Alamry, Al-attar, & Salih, 2022), (Jermins, 2016), (Kaunang & Walandouw, 2015), (Liawan & Harling, 2019), (Maulita, Adham, & Azizah, 2019), (Ningrum, Arafah, Darno, & Purnamasari, 2021), (Olayinka, 2022), (Putra, 2015), (Ramadhan & Mudzakar, 2022), (Ramdhani, Luthfiyani, & Afriani, 2020), (Sholihah & Agustina, 2020), (Syukriawati, Anhulaila, & Adam, 2015), (Wani, 2022). Berangkat dari data ini pula, pemateri memahami bahwa masih kurangnya sumbangsi pengembangan ilmu pengetahuan akuntansi berbasis kebudayaan lokal, Hal ini tentu sangat disayangkan, karena Indonesia merupakan negara yang memiliki keberagaman budaya, namun masih kurang dieksplor dan dilestarikan dalam ranah keilmuan akuntansi.…”
Section: Pendahuluanunclassified